Optimisation of a recombinant Hepatitis B vaccine through the cultivation and fermentation of Aspergillus Niger - James, Emmanuel Robin (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2005.